Tainui: A Case Study of Direct Negotiations - Mahuta, Robert Te Kotahi (Victoria University of Wellington Law Review, 1995)
This article explores the direct Treaty negotiation process in the context of the tribal history, the then-current thinking on Treaty of Waitangi claims, and the path that the author sees for Tainui. The author begins with the historical context to the Tainui, highlighting the injustices that the tribes suffered through raupatu (land confiscation) and warfare. The article then explores the Crown's attempts to provide redress followed by the negotiations. The result was the Ngai Tahu settlement claim in the South Island in March 1946. The author notes two issues in the negotiation process. First, there was the need for the government to admit that its invasion of the Waikato and subsequent confiscations were wrong. Secondly, there was the need for the government to return land or to otherwise provide the Waikato people with a secure economic base. The Coalcorp case, which provided an incentive for the claim to be placed at the negotiation table, is also briefly discussed (Tainui Māori Trust Board v Attorney-General [1989] 2 NZLR 513 (CA)). The result of that case was direct negotiation with the Crown, as well as some internal negotiation. As the negotiations had not been completed at the time of writing, the author concludes that Tainui's survival as a people rests on its desire to commit to a long-lasting and forward-thinking strategy. However, the author also argues that the outcome rests solely on the political will of both parties to settle.